HupB, a nucleoid-associated protein, is critical for survival of Mycobacterium tuberculosis under host-mediated stresses and for enhanced tolerance to key first-line antibiotics - Singh, Niti; Sharma, Nishant; Singh, Padam; Pandey, Manitosh; Ilyas, Mohd; Sisodiya, Lovely; Choudhury, Tejaswini; Gosain, Tannu Priya; Singh, Ramandeep; Atmakuri, Krishnamohan (Frontiers in Microbiology, 2022)
To survive and establish its niche, Mycobacterium tuberculosis (Mtb) engages a steady battle against an array of host defenses and the barrage of antibiotics. Here, we demonstrate that Mtb employs HupB, a nucleoid-associated protein (NAP) as its key player to simultaneously battle and survive at these two stress-inducing fronts. Typically, NAPs are key to bacterial survival under a wide array of environmental or host-mediated stresses. Here, we report that for Mtb to survive under different macrophage-induced assaults including acidic pH, nutrient depletion, oxidative and nitrosative stresses, HupB presence is critical. As expected, the hupB knockout mutant is highly sensitive to these host-mediated stresses. Further, Mtb aptly modulates HupB protein levels to overcome these stresses. We also report that HupB aids Mtb to gain tolerance to high levels of Rifampicin (RIF) and Isoniazid (INH) exposure. Loss of hupB makes Mtb highly susceptible to even short exposures of reduced amounts of RIF and INH. Overexpressing hupB in Mtb or complementing hupB in the hupB knockout mutant triggers enhanced survival of Mtb under these stresses. We also find that, upon loss of hupB, Mtb significantly enhances permeability of its cell wall by modulating levels of several surface lipids including Phthiocerol dimycocerosates (PDIMs), thus possibly influencing overall susceptibility to host-mediated stresses. Loss of hupB also downregulates efflux pumps expression possibly influencing increased susceptibility to INH and RIF. Finally, we find that therapeutic targeting of HupB with SD1, a known small molecule inhibitor significantly enhances Mtb susceptibility to INH and THP-1 macrophages, and significantly reduces MIC to INH. Thus, our data strongly indicates HupB as a highly promising therapeutic target especially for a potential combinatorial shortened therapy with reduced INH and RIF doses.